Cryoconite Hole Location in East-Antarctic Untersee Oasis Shapes Physical and Biological Diversity - Weisleitner, Klemens; Perras, Alexandra Kristin; Unterberger, Seraphin Hubert; Moissl-Eichinger, Christine; Andersen, Dale T.; Sattler, Birgit (Frontiers in Microbiology, 2020)
Antarctic cryoconite holes (CHs) are mostly perennially ice-lidded and sediment-filled depressions that constitute important features on glaciers and ice sheets. Once being hydrologically connected, these microbially dominated mini-ecosystems provide nutrients and biota for downstream environments. For example, the East Antarctic Anuchin Glacier gradually melts into the adjacent perennially ice-covered Lake Untersee, and CH biota from this glacier contribute up to one third of the community composition in benthic microbial mats within the lake. However, biogeochemical features of these CHs and associated spatial patterns across the glacier are still unknown. Here we hypothesized about the CH minerogenic composition between the different sources such as the medial moraine and other zones. Further, we intended to investigate if the depth of the CH mirrors the CH community composition, organic matter (OM) content and would support productivity. In this study we show that both microbial communities and biogeochemical parameters in CHs were significantly different between the zones medial moraine and the glacier terminus. Variations in microbial community composition are the result of factors such as depth, diameter, organic matter, total carbon, particle size, and mineral diversity. More than 90% of all ribosomal sequence variants (RSV) reads were classified as Proteobacteria, Cyanobacteria, Bacteroidetes, Actinobacteria, and Acidobacteria. Archaea were detected in 85% of all samples and exclusively belonged to the classes Halobacteria, Methanomicrobia, and Thermoplasmata. The most abundant genus was Halorubrum (Halobacteria) and was identified in nine RSVs. The core microbiome for bacteria comprised 30 RSVs that were affiliated with Cyanobacteria, Bacteroidetes, Actinobacteria, and Proteobacteria. The archaeal fraction of the core microbiome consisted of three RSVs belonging to unknown genera of Methanomicrobiales and Thermoplasmatales and the genus Rice_Cluster_I (Methanocellales). Further, mean bacterial carbon production in cryoconite was exceptionally low and similar rates have not been reported elsewhere. However, bacterial carbon production insignificantly trended toward higher rates in shallow CHs and did not seem to be supported by accumulation of OM and nutrients, respectively, in deeper holes. OM fractions were significantly different between shallower CHs along the medial moraine and deeper CHs at the glacier terminus. Overall, our findings suggest that wind-blown material originating south and southeast of the Anuchin Glacier and deposits from a nunatak are assumed to be local inoculation sources. High sequence similarities between samples from the Untersee Oasis and other Antarctic sites further indicate long-range atmospheric transport mechanisms that complement local inoculation sources.